Correlation of the effi ciency of endodontic treatment of posterior teeth and the value measure of the destruction of the occlusal surface occurring during the fi lling of root canals (LLC "Endo Press", 2020)
In case of endodontic treatment additional preparation should be carried out. This is done to ensure access to the mouths of the root canals. Quantity of volume remove hard tissue that is necessary to remove is a clinical and anatomical study. The best option of fi lling of root canal (not reaching to the top of 2 mm) was detected in the posterior depulped teeth with diff erent values of IDOST. However, this value was signifi cantly increased with the index IDOST (p < 0,05 t = 2,2). The cases with incomplete obturation of root canals decreases with increasing of IDOST (P12 < 0,05, t = 2,06), (R13 < 0,01, t = 3,12), (t = 1,01, R23 > 0,5). It was defected - that size of the defect determines the quality of the endodontic treatment. Data from these studies will help to predict methods of dental activities and make recommendations for action.